The Influence of Consumption of Carbohydrate to Adequacy Nutrition for Student of Elementary School Class 6 Tunas Karya Desa Karyawangi - Ramadhan, Reza (Universitas Pendidikan Indonesia, 2023)
Study this aim for knowing the influence of carbohydrate consumption to adequate nutrition of students grade 6 Tunas Karya Elementary School students Desa Karyawangi. Research conducted to 12 students, consisting of 7 boys and 5 girls with a range ages 10-12 years. As for the stages of research carried out, is (i) deployment pre-test questionnaire, (ii) giving education about the importance of carbohydrates for the body via powerpoint, and (iii) deployment post-test questionnaire. Analysis results show the mean pretest score was 66.7 and the post-test mean was 84.6. Comparison results from results between pre-test and post-test showed existence enhancement knowledge for students after holding education. Result of N-Gain calculation is known to have an average N-Gain value of 0.53 which states education about importance carbohydrate for body this not enough effective for student school base. Remember activity education is conducted only at meetings only, implications obtained are not effective and still many students who haven't once got education or eye lessons like this. from what we hope with existence study this education about importance carbohydrate or nutrition balanced more echoed return especially in children student school the basis for them understands importance consume carbohydrate for sufficient needs nutrition.